The effectiveness of the EU in the middle east peace process (mepp) and the role of Turkey - Metinulu, Sedat (My University, 2009)
Ortadoğu bölgesi dünya siyasetinde üzerinde en çok konuşulan bölgelerin başında gelmektedir. Bölgeyi bu kadar ilgi çekici hale getiren en önemli faktör devam etmekte olan İsrail ve Arap devletleri arasındaki uyuşmazlıktır. Bu bağlamda özellikle İsrail-Filistin mücadelesi ön plana çıkmaktadır. Tarihçesi altmış yıldan daha eskiye giden bu uyuşmazlığın çözümü için farklı platformlarda barışı sağlama çalışmaları yapılmıştır. Birleşmiş Milletler, Amerika Birleşik Devletleri ve Avrupa Birliği (AB), Orta Doğu Barış Süreci’nde en fazla adı geçen uluslararası aktörlerdir. Bu aktörlerin yanı sıra bölgede önemli yeri olan ülkelerin de barış sürecine katkıları olmaktadır. Türkiye sahip olduğu stratejik konumu, tarihsel arka planı ve geliştirmekte olduğu ikili ilişkiler bağlamında İsrail ve Filistin ile iyi ilişkiler içerisindedir. Barış sürecinin yol alabilmesi bölgedeki aktörlerin güven duyabileceği bir arabulucunun daha aktif rol almasıyla doğrudan ilgilidir. Bu çalışmanın birbiriyle ilişkili iki amacı bulunmaktadır. Bir taraftan AB’nin Orta Doğu Barış Süreci’ndeki rolünü ve etkinliğini analiz ederken diğer taraftan da Türkiye’nin bölgedeki konumuna, tarihsel bağlara ve ikili ilişkilerine vurgu yaparak barış sürecindeki rolünü yansıtmayı amaçlamaktadır. Bu çalışma Türkiye’nin Avrupa Birliği’ne girmesi durumunda AB’nin Ortadoğu politikasına ve barış sürecine nasıl katkı sağlayabileceğini dolaylı olarak göstermektedir. Ekonomik bir işbirliği bağlamında başlayan ancak bütünleşme sürecinin olumlu etkisiyle farklı alanlarda da ortak politikalar oluşturan Avrupa Birliği uluslar arası sistemde önemli bir aktör haline gelmektedir. AB’nin ortak dış ve güvenlik politikasının etkinliği kullanmış olduğu araçlarla doğrudan etkilidir. Orta Doğu Barış Süreci, Avrupa Birliği’nin aktörlüğünün ve dış politika araçlarının etkinliğinin analiz edilebileceği önemli bir laboratuardır. Sürecin dinamik yapısı ve AB’nin gelişmekte olan yapısı bu çalışmanın içeriğini etkileyen önemli bir faktördür. Bu çalışma AB’nin Orta Doğu Barış Süreci’ndeki etkinliğinin sınırlı olduğunu ve bölgedeki Amerikan politikalarının gölgesinde kaldığını savunmaktadır. Bu bağlamda Türkiye’nin AB üyeliğinin birlik için artı bir değer olacağını savunmaktadır.

The Middle East region is one of the popular regions in world politics. This is mainly because of the ongoing conflict between Israel and the Arab States, especially the Israeli-Palestinian conflict. The conflict has a history which is more than sixty year. There exist efforts in different platforms in order to establish peace in the region. The United Nations (UN), the United States of America (US) and the European Union (EU) are among the actors mentioned mostly in the Middle East Peace Process (MEPP). In addition to these actors, there are some regional actors that would contribute to the peace process. Turkey, for instance, has developed good relations with Israel and Palestine due to its geo-strategic position in the region, historical ties with them and significance of the bilateral agreements. The Development of the peace process is related to presence of an actor as the mediator who has been trusted by the parties in the conflict. There are two inter-related aims of this study. On the one hand, this study aims at to analyse the involvement and the effectiveness of the EU in the MEPP, on the other hand, it reflects the role of Turkey in the peace process by referring its position in the region, historical ties and the bilateral relations in the region. This study indirectly shows to what extent Turkey would contribute to the EU’s Middle East Policy and the Middle East Peace Process in case of membership to the Union. Thanks to the integration process of the Union, the EU has become an important actor in the international system which started as an economic cooperation and later developed common policies in different issues. The effectiveness of the Common Foreign and Security Policy (CFSP) of the EU is directly related to the tools available while dealing with third countries. In this context, the MEPP is an important laboratory to analyse the presence of the EU’s actorness and the effectiveness of the policy tools within the CFSP. Dynamic nature of the MEPP and the developing structure of the EU are the factors that affect the content of this study. This study argues that the EU’s effectiveness in the MEPP is limited and under the shadow of the US policies. In this context, the membership of Turkey to the Union would contribute to presence of EU as an effective actor in the peace process. TABLE OF CONTENTS ÖZET ii ABSTRACT iii TABLE OF CONTENTS iv LIST OF ABBREVIATIONS vi Introduction 1 I. The European Union as an Actor 8 1.1. Defining the EU as an actor 9 1.1.1. EU as a Unique Actor 10 1.2. How to approach EU’s Actorness 12 1.2.1. Constructivist approach to actorness 14 1.2.2. Dynamics of Actorness: opportunity, presence and capability 15 1.2.3. Inclusive and exclusive roles of the EU 19 1.3. The EU’s foreign policy instruments in dealing with third countries 21 1.4. Conclusion 27 II. The European Union and the Middle East Peace Process 30 2.1. The Roots of the Middle East Conflict 30 2.2. Significance of the Middle East for the EU 35 2.3. Explaining the EU efforts to end the Middle East Conflict 37 2.3.1. Legacy of the Past 38 2.3.2. Politics of the EU 38 2.3.3. Europe’s new security understanding 39 2.3.4. Choice between being “a payer or a player”? 40 2.3.5. The existence of the US in the region 40 2.3.6. The Religious dimension of the Conflict 41 2.4. The European involvement and role in the MEPP 42 2.5. Evaluation of the EU policy instruments in the MEPP 48 2.5.1. Venice declaration, June 1980 48 2.5.2. Madrid Peace Process 50 2.5.3. Oslo Accords 52 2.5.4. The Euro-Mediterranean Partnership 53 2.5.5. From Oslo to Second Intifada 55 2.5.6. September 11 and Iraq War 57 2.5.7. The Quartet and the Road Map 58 2.5.8. Recent developments 59 2.6. Understanding Transatlantic Division over the MEPP 61 2.7. Conclusion 64 III. Turkey and the Middle East Peace Process 66 3.1. Turkey and the Middle East 66 3.2. Turkey as a mediator in the MEPP 71 3.2.1. Turkey’s relations with Israel 74 3.2.1.1. Turkey’s Relations with Israel in the Cold War Era 75 3.2.1.2. Turkey’s Relations with Israel in the Post-Cold War Era 79 3.2.2. Turkey’s relations with Palestine 83 3.3. Policy divergences and convergences between Turkey and the EU regarding the MEPP 87 3.4. Turkey’s contribution to EU’s actorness and the MEPP 94 3.5. Conclusion 95 Conclusion 97 Appendix 103 Bibliography 105
Keywords: Avrupa Birliği_Türkiye; Dış İlişkiler_Türkiye